Characterization of single channel liquid light guide coupling and SPAD array imaging for tumour margin estimation using fluorescence lifetime. (30th September 2020) - Stewart, Hazel L; Hungerford, Graham; Birch, David J S
Abstract: Surgery remains one of the key treatment options for tumour removal, and surgeons primarily rely on eye and touch to assess the boundary between healthy and cancerous tissue with no cellular information as guidance. There is therefore a need for a device or instrument that can be used by the surgeon in real-time during the surgical procedure to ensure as many of the cancerous cells and as few of the healthy cells have been removed as possible. Fluorescence approaches have previously demonstrated significant promise in this application, but clinical take-up has been limited and much more characterization of critical parameters needed before robotic surgery can be contemplated. Here we investigate two time-correlated single-photon counting (TCSPC) fluorescence lifetime systems for the detection of phantom tumour margins derived from silica sol-gels. A simple and low-cost liquid light guide system (LLG) incorporating a single photomultiplier detection channel and translational stage was developed. This provided a useful reference for a compact single-photon avalanche diode (SPAD) array camera system for fluorescence lifetime imaging microscopy (FLIM) which permits up to ∼25 000 in-pixel timing measurements at video rates in ambient light using only low energy (∼30 pJ) diode laser pulses to minimize cell and dye degradation. Measurements of phantom margins with sol-gel doped Rhodamine 6G (R6G) of fluorescence lifetime ∼4 ns using the LLG system demonstrates that for 7 mm excitation diameter and over 5–15 mm sol-gel LLG separation the sol-gel only region could be clearly identified 1 mm after the margin position, a widely accepted minimum surgical resolution. A comparison between measurements with the LLG and SPAD FLIM system using the sub-ns fluorescence lifetime of the FDA-approved dye indocyanine green (ICG) demonstrates that the minimum workable spatial resolution and sufficient speed are only achievable with such faster lifetimes using the SPAD FLIM system.